Autodigestion: Proteolytic Degradation and Multiple Organ Failure in Shock. Issue 5 (May 2016) - Altshuler, Angelina E.; Kistler, Erik B.; Schmid-Schönbein, Geert W.
Abstract : ABSTRACT: There is currently no effective treatment for multiorgan failure following shock other than supportive care. A better understanding of the pathogenesis of these sequelae to shock is required. The intestine plays a central role in multiorgan failure. It was previously suggested that bacteria and their toxins are responsible for the organ failure seen in circulatory shock, but clinical trials in septic patients have not confirmed this hypothesis. Instead, we review here evidence that the digestive enzymes, synthesized in the pancreas and discharged into the small intestine as requirement for normal digestion, may play a role in multiorgan failure. These powerful enzymes are nonspecific, highly concentrated, and fully activated in the lumen of the intestine. During normal digestion they are compartmentalized in the lumen of the intestine by the mucosal epithelial barrier. However, if this barrier becomes permeable, e.g. in an ischemic state, the digestive enzymes escape into the wall of the intestine. They digest tissues in the mucosa and generate small molecular weight cytotoxic fragments such as unbound free fatty acids. Digestive enzymes may also escape into the systemic circulation and activate other degrading proteases. These proteases have the ability to clip the ectodomain of surface receptors and compromise their function, for example cleaving the insulin receptor causing insulin resistance. The combination of digestive enzymes and cytotoxic fragments leaking into the central circulation causes cell and organ dysfunction, and ultimately may lead to complete organ failure and death. We summarize current evidence suggesting that enteral blockade of digestive enzymes inside the lumen of the intestine may serve to reduce acute cell and organ damage and improve survival in experimental shock.